Przykłady karier akademickich kobiet na Uniwersytecie Poznańskim w okresie międzywojennym - Mazurczak, Dorota (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The long-lasting endeavors of the citizens of Wielkopolska to establish a Polish university in Poznañ eventually succeeded in January 1919. The Philosophical Faculty constituted the beginnings of Poznañ University (PU). The Legal and Economic Faculty, Faculty of Agriculture and Forestry and Medical Faculty followed soon after. In 1925, the Philosophical Faculty gave rise to two new ones, that of Humanities and the Faculty of Mathematics and Nature. In the first years of PU women were a definite minority of students in all faculties. The situation changed only in the last years preceding the outbreak of the Second World War. The number of female students in the Faculty of Humanities exceeded that of male students in 1936/37 and 1937/38 (427:345 and 387:324 respectively); the proportion of female students was also increasing in the Medical Faculty (233:747 and 228:688) and in the faculty of Mathematics and Nature the number of female students was approaching that of males (265:388 and 238:333), while there were only slightly over 200 females in the Legal and Economic Faculty (in comparison to 1505 and 1347 males). A few women were awarded doctoral degrees. In the time period between the academic years of 1920/21 and 1936/37 (inclusive) 1 woman out of 52 candidates defended a doctoral dissertation in the Legal and Economic Faculty, as did 35 women out of 147 individuals in the Faculty of Humanities, and 1 woman out of 57 candidates in the Faculty of Agriculture and Forestry. While the awarding of a doctoral degree to a woman was relatively common, receiving a postdoctoral degree (habilitacja) used to be a rare achievement. Granting the status of an independent academic, it was most frequent in female faculty members at the Medical Faculty of PU, where it was achieved by Helena Gajewska, Michalina Stefanowska, Anna Gruszecka, Eugenia Sto³yhwowa and Eugenia Piasecka-Zeylandowa. The status of an independent academic was also awarded to Ludwika Dobrzyñska-Rybicka (Philosophical Faculty) and Mieczys³awa Ruxerówna, Helena Polaczkówna and Bo¿ena Stelmachowska (Faculty of Humanities). Jadwiga Marszewska-Ziemiêcka obtained a postdoctoral degree in the Faculty of Agriculture and Forestry. Only three of the above obtained their professorships before the outbreak of the Second World War: Helena Gajewska (Full Professor), Ludwika Dobrzyñska-Rybicka and Michalina Stefanowska (Titular Professor). Four of the above women were married: Zeylandowa, Sto³yhwowa, Marszewska-Ziemiêcka and Dobrzyñska-Rybicka, who became a widow early on. The absence of family and household chores was likely to make a commitment to academic work easier; this could also be a price for achieving the status that went beyond the position of a housewife which was commonly assigned to women at the time.
Examples of Women’s Academic Careers at Poznań University in the Interwar Period